Forage Sorghum Silage Cost-Return Budget in South Central Kansas - Dhuyvetter, Kevin C. (My University, 2000)
The cost-return projection estimates the cost of producing forage sorghum silage in south central Kansas.
MF648_2000_10
Keywords: MF648; Economics; Crops; MF